Evaluation of the synergetic effect from implementation of economic activity by small business entities - Lukashova, Liudmyla (Technology audit and production reserves, 2019)
The object of research is the synergistic effect of economic activity by small entrepreneurship and the process of its formation. One of the most problematic places is the quantitative assessment of the synergistic effect. To eliminate this drawback allows the use of a list of methods used to determine the synergistic effect, in particular, the method of regression analysis. In the course of this research, the author classify the types of synergism according to the main classification criteria, such as profit components, types of assets, areas of human activity, sources of origin, scale of manifestation, duration of consequences of the manifestation of the synergistic effect. The applied methodology allows the author to justify the existence of a relationship between the main parameters that lead to the emergence of a synergistic effect from the implementation of economic activity by small entrepreneurship. As interrelated parameters, the number of types of economic activity of small entrepreneurship of individual entrepreneurs is considered, their income and tax burden. It was found that the synergistic effect manifests itself in the case of moderate and related diversification corresponds to the implementation of 2–5 types of economic activity by small entrepreneurship. Dependence is characterized as polynomial of the third degree. The presence of a synergistic effect is evidenced by an increase in revenue with a decrease in the tax burden and the predominance of revenue growth over the growth rate of the tax burden for groups. Thanks to the research, it becomes possible to determine the limit value of the number of types of economic activity of small entrepreneurship of individual entrepreneurs, providing a synergistic effect. The value of this indicator is 5. The author has proved that with an increase in the number of types of economic activity and an increase in the level of diversification of economic activity of small entrepreneurship, a gradual decrease in the synergistic effect is observed. The validity of the obtained results is confirmed by high reliability coefficients of the approximation R2, which are 0.98 (in terms of tax burden) and 0.99 (in terms of income).